Yield-per-Recruit, Utility-per-Recruit, and Relative Biomass of 21 Exploited Fish Species in China's Coastal Seas - Zhai, Lu; Pauly, Daniel (Frontiers in Marine Science, 2019)
Based on growth and related fishery parameters, three approaches, yield-per-recruit(Y/R), utility-per-recruit (U/R) analyses and relative biomass (B/B0) analyses were applied to 21 economically important, trawl-caught species in China’s coastal seas to estimate their relative yield, economic value and biomass under different schedules of fishing mortality and mean length at first capture. The results show that all species suffer from overfishing, given the high average fishing mortality (F~1 year-1) and small mesh size (~1 cm) used by trawlers. Long-term Y/R would double and U/R (expressed as price per landed weight) would increase 5-fold if mesh size were increased to about 10 cm. Comparing Y/R and U/R showed that the benefits of higher prices for larger individuals were detectable only if larger mesh sizes are used, so that individuals are caught only after they have been able to grow. The Y/R analyses also allowed estimating the biomass of the 21 assessed populations relative to their unexploited biomass, i.e., B/B0. Species-specific B/B0 values ranged from 0.01 to 0.58, with a mean of 0.16 (+/- 0.03), i.e., much lower than the 50% reduction corresponding to Maximum Sustainable Yield (i.e., B/BMSY =1), or B/B0 =0.5). This confirms the many authors who reported systematic overfishing along China’s coastlines, and suggests that rebuilding stocks should be the foremost goal of fisheries management in China.